PENGARUH METODE PEMBELAJARAN SURVEY, QUESTION, READ, RECITE, RIVIEW (SQ3R) BERBANTUAN KAMUS DIGITAL UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IV - Kurniasih, Tri; Unita, Imelda Free (Universitas Negeri Medan, 2024)
This study is motivated by the low learning outcomes of students in the Indonesian language subject in grade IV. The aim of this research is to determine the effect of the SQ3R method assisted by a digital dictionary on students' learning outcomes in the Indonesian language subject on the topic of Natural Beauty in grade IV at SDN 060863 Medan Timur. The study employs a two-group pretest-posttest design. The subjects of this research are class IV-A and IV-B, totaling 54 students. The data collection tool used is a pretest-posttest essay test instrument. The data analysis techniques used are normality tests, homogeneity tests, and hypothesis testing. The results of the study show an average increase of 44.63 in the experimental class and 29.82 in the control class. Based on the hypothesis test results conducted with a significance level of Î± = 0.05, the t-table value obtained is 2.063. Therefore, the criteria for drawing conclusions are t-calculated Ëƒ t-table, which is 5.61 Ëƒ 2.04. It can be concluded that Ha is accepted with the statement that there is an effect of using the SQ3R learning method assisted by a digital dictionary on students' learning outcomes in the Indonesian language subject on the topic of Natural Beauty in grade IV at SDN 060863 Medan Timur.Keywords: SQ3R Model, Learning Outcomes, Digital Dictionary